2014
DOI: 10.4103/0974-1208.138871
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic cystectomy of endometrioma: Good surgical technique does not adversely affect ovarian reserve

Abstract: BACKGROUND:The damage to ovarian reserve inflicted by surgery for endometriosis represents a major concern in the balance between reproductive benefits and risks.AIM:To evaluate the ovarian reserve in sub fertile women after laparoscopic endometriotic cystectomy.SETTINGS AND DESIGN:Prospective study, done in Department of Obstetrics and Gynecology, tertiary care hospital between August 2010-2012.MATERIALS AND METHOD:Laparoscopic cystectomy performed by stripping technique for endometriotic cysts. Endometriosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 19 publications
0
11
1
1
Order By: Relevance
“…Based on ultrasonographic findings (AFC, OvVol) and serum FSH levels, Bhat et al. also found that ovarian reserve did not show any significant changes at 1 month after laparoscopic cystectomy of endometrioma . In our study, no significant changes were found in either AFC or OvVol after cystectomy; however, a non‐statistically significant increase in the OvVol values was noted.…”
Section: Discussioncontrasting
confidence: 54%
“…Based on ultrasonographic findings (AFC, OvVol) and serum FSH levels, Bhat et al. also found that ovarian reserve did not show any significant changes at 1 month after laparoscopic cystectomy of endometrioma . In our study, no significant changes were found in either AFC or OvVol after cystectomy; however, a non‐statistically significant increase in the OvVol values was noted.…”
Section: Discussioncontrasting
confidence: 54%
“…According to the data from different studies, both laparoscopic techniques lead to reduction in ovarian volume and AFC as ultrasonographic markers for ovarian reserve. Several reports comparing cystectomy with puncture and endocoagulation have demonstrated that ablation was associated with a higher recurrence rate and lower cumulative pregnancy rate ( 2 , 3 , 4 , 5 , 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…A study by Bhat et al 16 including 73 patients who underwent laparoscopic cystectomy demonstrated an insignificant decline in the AFC 1 month postoperatively. The observation of this study was in contrast to our study that showed statistically significant decline in AFC of the operated ovary postoperatively.…”
Section: Discussionmentioning
confidence: 98%